Impact of haloazolisin production in the antiarchaeal activity of Haloferax mediterranei - Cassin, Elena (2023)
Halobacteria, also known as haloarchaea, is a class of halophilic Archaea living in hypersaline environments. Haloarchaea, similarly to all the extremophiles, possess a peculiar metabolism and have developed mechanisms that allow them to survive in harsh conditions, like high salinity, lack of nutrients and excessive UV exposure. Some of these adaptations lead to the production of a unique set of secondary metabolites, such as carotenoids, siderophores, polyhydroxyalkanoates, haloarchaeocins and ribosomally synthesized and post-translationally modified peptides (RiPPs). RiPPs produced by bacteria have been extensively studied because of their variety of structures and bioactivities, namely, as antibiotics, antivirals, antipain and morphogenetic compounds, but little is known about these peptides in Archaea. Recently, a group of biosynthetic gene clusters (BGCs), putatively encoding the production of RiPPs, were identified in the genome of various haloarchaea using bioinformatics tools and denominated haloazolins. These BGCs encode a cyclodehydratase belonging to the YcaO superfamily that install thiazole and oxazole heterocycles in their cognate peptides and, so far, none of them were experimentally investigated. Haloferax mediterranei ATCC 33500 is a haloarchaea able to inhibit growth of other haloarchaea and which encodes a haloazolisin BGC composed, at least, by the cyclodehydratase (ycaO) and its putative cognate peptide (haloA) genes. The main objective of this work was to investigate if this BGC could be involved in the anti-haloarchaea activity of H. mediterranei. Firstly, we have characterized H. mediterranei growth and the antagonistic activity along five days of growth in YPC agar, and it was concluded that maximum activity was reached after four days of incubation. At this timepoint, the transcriptional levels of ycaO and haloA were determined by RT-qPCR. Both genes were found to be transcribed, although not at the same level. Then, two knockout mutants, H. mediterranei ΔycaO and H. mediterranei ΔhaloA were generated with the pop-in/pop-out method and their antagonistic activity was tested. The deletion of the genes did not influence the production of biomass and ΔycaO and ΔhaloA mutants retained their anti-haloarchaea activity. However, ΔycaO displayed a slightly increased inhibition, whereas ΔhaloA showed a slightly reduced activity compared to the wildtype. Thus, the haloazolisin BGC does not encode the main antimicrobial molecule(s) produced by H. mediterranei, which remains unknown. Additionally, these results suggest that other peptide(s)/protein(s), and not exclusively HaloA, might be a substrate(s) for the YcaO enzyme. Also, they raised some doubts about whether HaloA is the cognate peptide of this enzyme. So, further experimental studies are needed to characterize the antimicrobial molecules produced by H. mediterranei and to understand the cellular function of YcaO and HaloA.